2012
DOI: 10.1037/a0027010
|View full text |Cite
|
Sign up to set email alerts
|

Culture and the body: East–West differences in visceral perception.

Abstract: This research investigated cross-cultural differences in the accuracy of individuals' perceptions of internal visceral states. We conducted 4 studies to test the hypothesis that Asians are less sensitive to internal physiological cues relative to European Americans. Studies 1 and 2 assessed cultural differences in visceral perception via tests of misattributions of arousal: Study 1 involved false heart rate feedback during an emotionally evocative slideshow and examined subsequent self-reported affective chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 73 publications
1
49
1
Order By: Relevance
“…Culture-specific effects with respect to the perception and cognitive processing of signals arising from within the body have been repeatedly described. 68 While members of Western societies exhibited higher interoceptive accuracy in laboratory studies compared to people from non-Western societies, non-Western cultures tend to demonstrate heightened somatic focus and greater emphasis on their bodily states when describing emotional experiences. 68 16 controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture-specific effects with respect to the perception and cognitive processing of signals arising from within the body have been repeatedly described. 68 While members of Western societies exhibited higher interoceptive accuracy in laboratory studies compared to people from non-Western societies, non-Western cultures tend to demonstrate heightened somatic focus and greater emphasis on their bodily states when describing emotional experiences. 68 16 controversial.…”
Section: Discussionmentioning
confidence: 99%
“…68 While members of Western societies exhibited higher interoceptive accuracy in laboratory studies compared to people from non-Western societies, non-Western cultures tend to demonstrate heightened somatic focus and greater emphasis on their bodily states when describing emotional experiences. 68 16 controversial. It has been shown that interventions such as relaxation and mindfulness training do not substantially alter heartbeat perception.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the concept of self in Eastern cultures is more socially oriented, yielding what is described as 'interdependent self' (Markus and Kitayama 1991;Kitayama and Park 2010). Moreover, Eastern cultures seem to be less accurate in perceiving changes in the own internal physiological state while being more driven by contextual external than interoceptive cues (Ma-Kellams et al 2012).…”
Section: Psychiatric Evidence Ib: Cultural Differences In Depressive mentioning
confidence: 91%
“…This is even more important to consider given the fact that psychological studies (Markus and Kitayama 1991;Markus and Kitayama 2003) demonstrate differences in IA and EA and self-referential processing between Eastern and Western cultures (Ma-Kellams et al 2012).…”
Section: Psychiatric Evidence Ib: Cultural Differences In Depressive mentioning
confidence: 99%
“…Thus, the conscious, phenomenal map may not be the same as the broader simulation map, although we view the simulation map as necessary for phenomenal bodily experience. Furthermore, there is large inter-individual variability among phenomenal maps as a function of goals, culture, personal experience, and possibly genetics and other contributing factors (Ferron, 1997;Altabe, 1998;Ma-Kellams et al, 2012;Maister and Tsakiris, 2014). These factors may combine to limit how the simulation map is consciously accessed, and a history of biased simulation map access may override momentary introspective efforts.…”
Section: Regulation Through Simulationmentioning
confidence: 99%